Divining Disaster. Signs of Catastrophe in Ancient Greek Culture - Veldhuizen, Michiel van (Classical Studies E-Books Online, Collection 2025., 2025)
In a world riddled with earthquakes and plagued by epidemics, how did the ancient Greeks cope with, and make sense of, disaster? As our present-day environment is perceived to be increasingly perilous, this book includes the ancient Greek world in the longue durée of disaster discourse. Drawing on anthropological disaster studies, ecocriticism, and cognitive studies, this study considers disaster as a semiotic phenomenon marked by uncertainty. Divining disaster, then, functions as a hermeneutic form of disaster management that alleviates uncertainty and assigns agency, not only in religious practices such as oracle consultation but also in historical and mythological narratives.